2011
DOI: 10.1002/cbf.1741
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotector effect of p,p'‐methoxyl‐diphenyl diselenide in a model of sporadic dementia of Alzheimer's type in mice: contribution of antioxidant mechanism

Abstract: The present study investigated whether the antioxidant activity of p,p'-methoxyl-diphenyl diselenide [(MeOPhSe)(2)] is involved in its protective effect against cognitive impairment induced by streptozotocin (STZ) in a model of sporadic dementia of Alzheimer's type (SDAT). Swiss mice were treated with STZ or vehicle [2 µl of 2·5 mg ml(-1) solution; intracerebroventricularly (i.c.v.)] twice, 48 h apart. (MeOPhSe)(2) (25 mg kg(-1)) or vehicle was orally administered 30 min prior to each STZ treatment. Neuroprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…These results suggest that the antioxidant property could be involved in the (MeOPhSe) 2 neuroprotective effect on SDAT induced by STZ in rats. Accordingly, the neuroprotective effect of the antioxidant (MeOPhSe) 2 was reported [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results suggest that the antioxidant property could be involved in the (MeOPhSe) 2 neuroprotective effect on SDAT induced by STZ in rats. Accordingly, the neuroprotective effect of the antioxidant (MeOPhSe) 2 was reported [19].…”
Section: Discussionmentioning
confidence: 99%
“…There have also been data indicating the involvement of oxidative stress in STZ-induced SDAT model [12,23]. Based on these positive results [19,20], we planned this study to investigate the therapeutic effect of (MeOPhSe) 2 against STZ-induced SDAT model. The involvement of AChE activity, deficit in cerebral energy metabolism, and oxidative and nitrosative stress in the therapeutic effect of (MeOPhSe) 2 in the cognitive impairment induced by STZ was examined.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…), 21-day treatment alone, while its combination with subeffective dose of sesamol (4 mg/kg) potentiated its protective effect (Misra et al 2011), confirming that modulation of nitrite signalling and the oxide-inflammatory cascade might provide therapeutic effects in an AD condition. Selenium (Se), a nutritionally essential trace element with known antioxidant potential, protects the brain from oxidative damage in various models of neurodegeneration As already mentioned, neuroprotective effect of organoselenium (MeOPhSe)(2) administered orally (25 mg/kg) 30 min prior to STZ-icv injection in mice was manifested in cognitive improvement in the Y-maze test associated with an anticholinesterase efficacy (Pinton et al 2010) but additional experiments demonstrated that its neuroprotection in the STZ-icv model is due to its antioxidant activity as well (Pinton et al 2011). Pretreatment supplementation with sodium selenite, a salt of Se (0.1 mg/kg p.o.…”
Section: Compounds With Predominant Antioxidative Activity Often Accmentioning
confidence: 98%
“…Recent experimental studies using a wide range of antioxidants including P-P methoxydiphenyl diselenide (Pinton et al, 2011), S allyl cysteine (Javed et al, 2011), conjugates of ibuprofen and glutathione (Pinnen et al, 2011), tirilazad , Ibuprofen and lipoic acid (Distefano et al, 2010), and chlorogenic acid (Kwon et al, 2010), have shown neuroprotective effects in animal models of AD. On the other hand mitochondria specific antioxidants such as acetyl-L-carnitine and R-alpha lipoic acid have been suggested to be beneficial for treatments for AD (Palacios et al, 2011).…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%